Scalene triangle
because all sides are of a different length
Answer:
17
Step-by-step explanation:
Answer: B
Step-by-step explanation:
-3x^2-9xi+9ix-27
-3x^2-27
What is the question you are asking and no one is gonna know what lesson 3.2 means.
Answer:
x = -2
Step-by-step explanation:
For this problem, we must simply solve for x. To do this, we will need equation operations, and the use of the distributive property.
Let's work this line by line until we have the value for x:
3{-x + (2x + 1)} = x - 1
3*-x + 3*(2x + 1) = x - 1
-3x + 6x + 3 = x - 1
3x + 3 = x - 1
2x = -4
x = -2
Now we can check our answer for x by plugging back into the original equation and see if the left hand side is equal to the right hand side:
3{-x + (2x + 1)} = x - 1
3{-(-2) + (2(-2) + 1)} ?= (-2) - 1
3{2 + (-4 + 1)} ?= -3
3{2 + (-3)} ?= -3
3{-1} ?= -3
-3 == -3
Thus, we have found the solution for x to be equivalent to negative 2.
Cheers.